Medical Informatics and the Quality of Health: New Approaches to Support Patient Care - Ammenwerth, E.; Haux, R.; Kulikowski, C.; Bohne, A.; Brandner, R.; Brigl, B.; Fischer, G.; Garde, S.; Knaup, P.; Ruderich, F.; Schubert, R.; Singer, R.; Wolff, A. C. (Methods of Information in Medicine, 2003)
Objectives: The Yearbook of Medical Informatics is published annually by the International Medical Informatics Association (IMIA) and contains a selection of excellent papers on medical informatics research which have been recently published (www.yearbook.uni-hd.de). The 2003 Yearbook of Medical Informatics took as its theme the role of medical informatics for the quality of health care. In this paper, we will discuss challenges for health care, and the lessons learned from editing IMIA Yearbook 2003.Results and Conclusions: Modern information processing methodology and information and communication technology have strongly influenced our societies and health care. As a consequence of this, medical informatics as a discipline has taken a leading role in the further development of health care. This involves developing information systems that enhance opportunities for global access to health services and medical knowledge. Informatics methodology and technology will facilitate high quality of care in aging societies, and will decrease the possibilities of health care errors. It will also enable the dissemination of the latest medical and health information on the web to consumers and health care providers alike. The selected papers of the IMIA Yearbook 2003 present clear examples and future challenges, and they highlight how various sub-disciplines of medical informatics can contribute to this.
Keywords: Medical Informatics; IMIA Yearbook; Evaluation; Health Technology Assessment; Quality of Health Care